Malay Wedding Hantaran Pantun in West Kalimantan: The Preservation of Malay–Islamic Admonitions as Traditional Cultural Imagery - Rahmat; Ikhza Mahendra Putra; Agus Wartiningsih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines the cultural and religious values embedded in hantaran pantun recited during the Malay wedding gift-giving procession in Pontianak, Sambas, and Melawi, West Kalimantan. Although pantun plays a central role in Malay ceremonial life, limited studies integrate cultural semantics and metaphor analysis to explain how these verses transmit worldview and moral norms in performative contexts. A total of 46 pantun was collected through participant observation, interviews, and audio recordings, from which six were selected for in-depth analysis based on representativeness and symbolic density. Using a qualitative descriptive design, the study applies cultural semantic analysis and metaphorical examination of both sampiran and isi lines to interpret meanings from emic and etic perspectives. The findings identify six core admonitory values: respect for tradition, honor and humility, remembrance of Allah, honesty, friendliness, and social harmony. These values construct a relational worldview that emphasizes ethical responsibility toward self and community. The study contributes by integrating cultural semantics with metaphor analysis in oral tradition research and supports cultural preservation and value-based education in Malay society.